2004
DOI: 10.1177/0091270004269582
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In Vivo CYP2D6 Activity: Differential Sensitivity of Commonly Used Probes to Urine pH

Abstract: Drug/metabolite ratios (MRs) are used as in vivo markers of enzyme activity. The ratios are potentially confounded by the renal clearance of the drug (urine-based MRs) or metabolite (plasma-based MRs). The authors have investigated the relative sensitivity of urinary MR of 3 in vivo probe substrates of CYP2D6 debrisoquine (DB), dextromethorphan (DM), and metoprolol (MP) to changes in urine pH. Three groups of healthy volunteers each comprising 12 individuals were given DB (10 mg), DM (25 mg), or MP (100 mg) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Only *3, *4, *5, *6, *9, *10, *41 and *1ϫN CYP2D6 polymorphisms were investigated. Stamer et al recently documented that *45 and *46 CYP2D6 polymorphisms also contributed to the interindividual variability of enantiomer-specific tramadol metabolism in adults (19). Based on the overall low incidence of *45 and *46 polymorphism in whites (Ͻ2%), it is to be anticipated that the impact of these CYP2D6 polymorphisms is limited (22).…”
Section: Discussionmentioning
confidence: 99%
“…Only *3, *4, *5, *6, *9, *10, *41 and *1ϫN CYP2D6 polymorphisms were investigated. Stamer et al recently documented that *45 and *46 CYP2D6 polymorphisms also contributed to the interindividual variability of enantiomer-specific tramadol metabolism in adults (19). Based on the overall low incidence of *45 and *46 polymorphism in whites (Ͻ2%), it is to be anticipated that the impact of these CYP2D6 polymorphisms is limited (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no such pronounced inhibition, propiverine effects on CYP1A2 were also evaluated, prompted by recent additional data (Walter et al, 2003). We also decided to evaluate the effects on CYP2D6, but these results will be reported separately because extensive additional evaluations are required to assess the validity of dextromethorphan metabolic ratios in urine and plasma for the quantification of drug-drug interactions (Streetman et al, 2000a;Ö zdemir et al, 2004;Borges et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the phenotyping protocol, the key issues are the choice of the analyte and the assay technique. Given the susceptibility of urinary metoprolol or dextromethorphan metabolic ratio to changes in urinary pH [121], alternative in vivo markers of CYP2D6 with low susceptibility to changes in urinary pH, such as point estimates from plasma concentrations or breath test, are to be highly preferred. Hu et al [122] have shown that the plasma sample at 2, 3, 4 or 5 h or the saliva sample at 6 h could be used for determining the DMR.…”
Section: Phenotyping Protocolsmentioning
confidence: 99%